Pengaruh Disruptive Innovation Terhadap Pendidikan Di Akademi Militer Pada Era Society 5.0 - Muhammad Irfan; Agustina Dwi MP; Novega Galih Armyanto; Raihan Muhammad Rifqi; Satria Nawal Azka; Muhammad Abdul Ghofur (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Increasing Military Academy as an educational institution must be able to receive the era of 5.0 societies properly. This educational institution has the best way to take the advantage of disruptive innovations among others is to integrate disruptive innovation in learning methods that provide the ability to deal with complex problems and utilize the latest technology to improve the quality of students effectively and efficiently.